Pengaruh Leverage, Profitabilitas, Ukuran Perusahaan Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan ( Studi Emperis Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bei Tahun 2016-2022) - Fadzilla Isnaini Puspitasari; Sunarto Sunarto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine and analyze the factor that influence firm value. Some of the variables used in this study are leverage, profitability, company size, and company growth. The population used in this study are companies in the real estate and property sector that are listed on the Indonesia Stock Exchange in 2016-2022. The method used to collect this data is purposive sampling method. The number of samples used is 46 companies and the number used is 322 data. When processing data, there are several company data that must be outlier. After the outlier data, the number of samples used was 143 data. The analytical method used in this study is the quantitative analysis method. The results of this study show that leverage and company growth have no effect on firm value. While the profitability and size of the company positive affect the value of the company. Keywords: Leverage, Profitability, Company Size, Company Growth, and Company Value